2020
DOI: 10.1038/s41598-020-65564-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific Electrogram Characteristics Identify the Extra-Pulmonary Vein Arrhythmogenic Sources of Persistent Atrial Fibrillation – Characterization of the Arrhythmogenic Electrogram Patterns During Atrial Fibrillation and Sinus Rhythm

Abstract: Identification of atrial sites that perpetuate atrial fibrillation (AF), and ablation thereof terminates AF, is challenging. We hypothesized that specific electrogram (EGM) characteristics identify AF-termination sites (AFTS). Twenty-one patients in whom low-voltage-guided ablation after pulmonary vein isolation terminated clinical persistent AF were included. Patients were included if short RF-delivery for <8sec at a given atrial site was associated with acute termination of clinical persistent AF. EGM-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 22 publications
3
49
0
3
Order By: Relevance
“…Previous studies have shown that AF driver sites with acute AF termination frequently occur within LVA in bipolar mapping (Jadidi et al, 2016(Jadidi et al, , 2020. Considering our findings, atrial sites displaying low voltage in the bipolar map will also display these regions in the unipolar map, thus indicating that an important criterion for AF source localization during high-density Lasso mapping is reduced electrogram voltage irrespective of the mapping modality (uni-/bipolar).…”
Section: Main Findingssupporting
confidence: 67%
See 2 more Smart Citations
“…Previous studies have shown that AF driver sites with acute AF termination frequently occur within LVA in bipolar mapping (Jadidi et al, 2016(Jadidi et al, , 2020. Considering our findings, atrial sites displaying low voltage in the bipolar map will also display these regions in the unipolar map, thus indicating that an important criterion for AF source localization during high-density Lasso mapping is reduced electrogram voltage irrespective of the mapping modality (uni-/bipolar).…”
Section: Main Findingssupporting
confidence: 67%
“…Presence and accurate localization of low voltage areas was confirmed by contact force-sensing catheters (>5 g). Bipolar low voltage zones were defined as <0.35 or <0.5 mV in AF, according to the findings in recent studies (Jadidi et al, 2016(Jadidi et al, , 2020Rodríguez-Mañero et al, 2018).…”
Section: Voltage Mapping In Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis represents a complex structure comprised of different factorssuch as collagen deposition, inflammatory cytokines, proteins, among othersthat alter the electrophysiology of the cardiac tissue. For instance, heterogeneities induced by the presence of fibrosis alter conduction patterns in the cardiac tissue, creating regions of slow and anisotropic conduction [4]. Such delayed activation might favor the occurrence of re-entrant activity, which in turn participates in the perpetuation of the arrhythmia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such delayed activation might favor the occurrence of re-entrant activity, which in turn participates in the perpetuation of the arrhythmia [5]. The relationship between rotors and fibrosisas well as rotor detection related to fibrosisremains controversial [4]. Additionally, methods for automated rotor detection during cardiac electrophysiologic studies rely mostly on unipolar measurements, whereas the majority of clinical centers perform AF ablation guided by attributes extracted from bipolar electrograms (EGMs) [2].…”
Section: Introductionmentioning
confidence: 99%